Defisiensi Zat Gizi Makro dan Zat Gizi Mikro Saat 1000 Hari Pertama Kehidupan Berdampak pada Obesitas Usia Dewasa - Cevin Rosse Octaviane; Ahmad Syafiq (Syntax Corporation, 2023)
Stunting is a major nutritional problem worldwide that occurs due to deficiencies of macronutrients and micronutrients during the first 1000 days of life. Stunting can affect brain development and cognitive development of children. Stunting increases the risk of obesity as an adult. This study aims to analyze the deficiency of macronutrients and micronutrients during the first 1000 days of life impact adult obesity. This study uses a literature review. Three electronic database are used : Google Scholar, PubMed Central and ScienceDirect. The article used in this research are 8 articles. The inclusion criteria for this study were articles published within ten years, namely, 2013-2022, full text, open access, and in Indonesian and English. Deficiencies of macronutrients such as energy and protein as well as deficiencies of micronutrients such as iron, zinc, folic acid and iodine affect the regulation of cell division growth factors such as the insulin growth factor-1, low hormone levels can interfere with lipolysis, so that stunted children can experience obesity in adulthood due to low metabolic rate. The fulfillment of nutrition in the First 1000 days of life is very important for the growth and development of children